Effects of central metals on sugar decorated tetrakis-(4-methylthiophenyl) porphyrin considered for use in photodynamic therapy - Thembani Silas Vukeya; Refilwe Matshitse; John Mack; Yolande Openda; Earl Prinsloo; Tebello Nyokong (Photodiagnosis and Photodynamic Therapy)
This study focuses on the synthesis of sugar decorated porphyrins and their gold nanoparticle conjugates as photosensitizers for photodynamic therapy (PDT). Linking the sugar to the porphyrins imparted water solubility to the latter. The conjugation to sugar molecules enhanced the singlet oxygen quantum yield and improved the cellular uptake and therefore, their phototoxicity in some cases. The porphyrins (with or without the sugar) were linked to the Au nanoparticles (AuNPs). The activity of the synthesized complexes and conjugates with AuNPs were tested against the MDA-MB-231 breast cancer cells using the resazurin assay to monitor the cell viability. The conjugate of In porphyrin with AuNPs showed the highest PDT activity.